Nutrient and antinutrient composition of winged bean (Psophocarpus tetragonolobus (L.) DC.) seeds and tubers - Adegboyega, T.T.; Abberton, Michael T.; AbdelGadir, Abdel Aziz H.; Dianda, M.; Maziya-Dixon, Busie; Oyatomi, O.A.; Ofodile, S.; Babalola, O.O. (Hindawi Limited, 2019)
Many people in sub-Saharan Africa suffer from protein malnutrition; this results in negative health and economic impacts. Winged bean (Psophocarpus tetragonolobus (L.) DC.) is a tropical underutilized legume with beneficial nutritional characteristics such as high protein content, which may help to alleviate these problems. The proximate composition (fat, moisture content, crude protein, ash, and carbohydrate) and antinutrient (tannin and phytate) level of winged bean seeds and tubers were determined using 50 accessions. In the processed seeds, accession Tpt17 had the highest protein content (40.30%) and Tpt48 the lowest (34.18%). In the unprocessed seeds, Tpt17 also recorded the highest crude protein (31.13%) with Tpt125 having the lowest (28.43%). In the tubers, protein content ranged from 19.07% (Tpt42) to 12.26% (Tpt10). The moisture content in the processed seeds ranged from 8.51% (Tpt42) to 6.72% (Tpt6); in the unprocessed seeds, it was between 8.53% (Tpt53) and 3.76% (Tpt14). In the processed seeds, the values of ash ranged from 4.93% (Tpt126) to 4.45% (Tpt15-4); in the unprocessed seeds, it ranged from 4.98% (Tpt17) to 4.55% (Tpt125). In the processed seeds, the fat content ranged from 18.91% (Tpt51) to 14.09% (Tp43) while in the unprocessed seeds, the values ranged from 19.01% (Tpt15) to 13.87% (Tpt3-B). The crude fiber in the processed samples ranged from 13.82% (Tpt6) to 10.40% (Tpt125) while in the unprocessed seeds, it ranged from 7.29% in Tpt51 to 4.83% in Tpt11. Carbohydrate content in the processed seeds ranged from 26.30% (Tpt3-B) to 20.94% (Tpt125) and 39.76% in Tpt3-B to 34.53% in Tpt18 in the unprocessed seeds. The tannin and phytate contents showed remarkably significant differences. In the tubers harvested, significant variation was observed in the parameters evaluated. Winged bean flour could be formulated into various meals for children and adults to reduce malnutrition in sub-Saharan Africa.